Find expert advice and community support for all your questions on IDNLearn.com. Our Q&A platform offers reliable and thorough answers to help you make informed decisions quickly and easily.
Sagot :
[tex]▪▪▪▪▪▪▪▪▪▪▪▪▪ {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪[/tex]
As we know, the standard form of circle is written in this way ~
[tex] \qquad \sf x{}^{2} + y {}^{2} + 2gx + 2fy + c = 0[/tex]
where, the coordinates of centre is (-g , -f) and radius equals to :
[tex]\qquad \sf \dashrightarrow \: \sqrt{g {}^{2} + {f}^{2} - c } [/tex]
Now, it's time to equate the coordinates of centre ~
- [tex] \qquad \sf( - g, - f) \: \: and \: \: (0,4)[/tex]
Here we get,
[tex]\qquad \sf \dashrightarrow \: - g = 0[/tex]
[tex]\qquad \sf \dashrightarrow \: g = 0[/tex]
and
[tex]\qquad \sf \dashrightarrow \: - f = 4[/tex]
[tex]\qquad \sf \dashrightarrow \: f = - 4[/tex]
Now, let's find the the Radius using distance formula on the given points, one of them is centre and other is point lying on circle, so distance between them is the radius.
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{( 0 - ( - 2)) {}^{2} + (4 - ( - 4)) {}^{2} }[/tex]
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{ (0 + 2) {}^{2} + (4 + 4) {}^{2} } [/tex]
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{ (2) {}^{2} + (8) {}^{2} } [/tex]
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{ 4+ 64 } [/tex]
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{ 68 } [/tex]
[tex]\qquad \sf \dashrightarrow \: r = 2\sqrt{ 17 } [/tex]
Now, use the the following equation to find c of the standard equation
[tex]\qquad \sf \dashrightarrow \: r = \sqrt{g {}^{2} + {f}^{2} - c} [/tex]
[tex]\qquad \sf \dashrightarrow \: 2 \sqrt{17} = \sqrt{ {0}^{2} + {4}^{2} - c}[/tex]
squaring both sides :
[tex]\qquad \sf \dashrightarrow \: 68 = {0}^{2} + {4}^{2} - c[/tex]
[tex]\qquad \sf \dashrightarrow \: 68 = 8 - c[/tex]
[tex]\qquad \sf \dashrightarrow \: - c = 68 - 8[/tex]
[tex]\qquad \sf \dashrightarrow \: c = - 60[/tex]
Therefore, we got the standard equation of circle as ~
[tex]\qquad \sf \dashrightarrow \: {x}^{2} + {y}^{2} + 2(0)x + 2( - 4)y + ( - 60) = 0[/tex]
[tex]\qquad \sf \dashrightarrow \: {x}^{2} + {y}^{2} - 8y - 60 = 0[/tex]
I Hope it helps ~
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is your reliable source for accurate answers. Thank you for visiting, and we hope to assist you again.